2022
DOI: 10.3390/toxins14070473
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Species and Multi-Mycotoxin Associated with Post-Harvest Sorghum (Sorghum bicolor (L.) Moench) Grain in Eastern Ethiopia

Abstract: Sorghum is the main staple food crop in developing countries, including Ethiopia. However, sorghum grain quantity and quality are affected by contaminating fungi both under field and post-harvest stage. The aim of the current study was to assessed fungal species and multi-mycotoxins associated with sorghum grain in post-harvest samples collected from eastern Ethiopia. Fungal genera of Aspergillus, Alternaria, Bipolaris, Fusarium, Mucor, Penicillium, and Rhizoctonia were recovered in the infected grain. A liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…So far, more than 400 different fungal toxins have been identi ed, among which most common and harmful are A atoxin (AFT), Zearalenone (ZEN), Fumonisin (FB), Deoxynivalenol (DON) and T-2 toxin (T-2 toxin). -2 toxin (T-2) [5] . Studies [6] have shown that mycotoxins are most frequently noti ed risk category, accounting for about 21% of all noti cations since 1981.…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than 400 different fungal toxins have been identi ed, among which most common and harmful are A atoxin (AFT), Zearalenone (ZEN), Fumonisin (FB), Deoxynivalenol (DON) and T-2 toxin (T-2 toxin). -2 toxin (T-2) [5] . Studies [6] have shown that mycotoxins are most frequently noti ed risk category, accounting for about 21% of all noti cations since 1981.…”
Section: Introductionmentioning
confidence: 99%
“…The highest number of co-occurring mycotoxins was 12 mycotoxins in the form of the mixture: AOH + AME + TeA + TEN + ENA1 + ENB + ENB1 + BEA + MON + DAS + NIV + STC found in sorghum from Ethiopia [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researches carried out in other regions have discovered a similar trend. For instance, the same group of isolates stated above were isolated from sorghum grains collected in Eastern Ethiopia while proposing that variation in fungal population may be caused by a complex interaction of factors available during sorghum growth on the field, during harvest, and storage practices used [15].…”
Section: Resultsmentioning
confidence: 99%
“…Sorghum grains are often contaminated by moulds, mostly colonising the surface, causing physical damage and posing a serious biotic limitation in sorghum production areas [6]. Several of these fungi are either facultative parasites or saprophytic fungi, contributing to pre-and post-harvest deterioration of grains [8]. Environmental conditions of temperature and humidity which are prevalent in most of the areas of cultivation, favour the growth and metabolism of these fungi.…”
Section: Introductionmentioning
confidence: 99%